Protection of children’s rights in Omani legislation in the light of the rules of international law - Al-Siyabi, AbdulRahim Yahya Khalfan; Amin ِAbdulillah (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aimed to clarify the role of the Omani legislator in protecting the rights of the child in the Sultanate compared to the international legislation related to the protection of the rights of the child. In that, the researcher used the comparative analytical approach by explaining the concept of the child in international law and Omani legislation. Then, the study touched on some international legislation that focused on the protection of human rights in general and the protection of children’s rights, and what is the position of the Omani legislator on these international legislations regarding to the protection of children’s rights. The problem of the study was the question of the compatibility of the Omani national legislation with the international legislation in achieving the required protection of the rights of the child and the questions that arise from it. The study concluded with results, the most important of which is that the Convention on the Rights of the Child is a turning point in human history, as it is the first binding agreement that deals with the rights of the child fully and in detail, and that the Omani Child Law is a milestone in the system of laws that provide protection for the rights of the Omani child.